Biomechanical comparison of single‐row, double‐row, and transosseous‐equivalent repair techniques after healing in an animal rotator cuff tear model. Issue 8 (9th April 2013) - Quigley, Ryan J.; Gupta, Akash; Oh, Joo‐Han; Chung, Kyung‐Chil; McGarry, Michelle H.; Gupta, Ranjan; Tibone, James E.; Lee, Thay Q.
Abstract The transosseous‐equivalent (TOE) rotator cuff repair technique increases failure loads and contact pressure and area between tendon and bone compared to single‐row (SR) and double‐row (DR) repairs, but no study has investigated if this translates into improved healing in vivo. We hypothesized that a TOE repair in a rabbit chronic rotator cuff tear model would demonstrate a better biomechanical profile than SR and DR repairs after 12 weeks of healing. A two‐stage surgical procedure was performed on 21 New Zealand White Rabbits. The right subscapularis tendon was transected and allowed to retract for 6 weeks to simulate a chronic tear. Repair was done with the SR, DR, or TOE technique and allowed to heal for 12 weeks. Cyclic loading and load to failure biomechanical testing was then performed. The TOE repair showed greater biomechanical characteristics than DR, which in turn were greater than SR. These included yield load (p < 0.05), energy absorbed to yield (p < 0.05), and ultimate load (p < 0.05). For repair of a chronic, retracted rotator cuff tear, the TOE technique was the strongest biomechanical construct after healing followed by DR with SR being the weakest. © 2013 Orthopaedic Research Society Published by Wiley Periodicals, Inc. J Orthop Res 31:1254–1260, 2013